(untitled) (Asian-Australasian Journal of Food Safety and Security, 2018)
The study was conducted to determine the fish retailer’s livelihood and socio-economic status in three markets of Jashore for a period of six months from February to August, 2016. The average net profit of fish retailers was found higher in Boro bazaar (Tk.350) followed by Palbari bazaar (Tk.325), Chuadanga Bus Stand bazaar (TK.275). The average age groups of 20-65 years were found among the markets. The study shows that 53% fish retailers had nuclear family and 47% had joint family. Most of the housing conditions were kacha (69%) and Muslim fish retailers were predominant in all markets. Among the total 45 traders interviewed, 42% were illiterate, 31% have primary level education, 24% have secondary level education and none of them had bachelor level of education. It was found that fish retailers of Boro bazaar and Palbari bazaar sold an average of 35 kg fish daily, compared with Chuadanga Bus Stand bazaar 15 kg per day. The daily supply of fish in Boro bazaar can be estimated at 1.6 MT (25 retailers’ × 65 kg) while 0.3 MT (15 retailers × 20 kg) and 0.45 MT (15 retailers × 30 kg) in C.B Bazar and Palbari bazaar respectively. Improvement in basic infrastructure such as, clean water supply, sanitation facilities, adequate drainage and ice facilities are recommended by the present study. Asian Australas. J. Food Saf. Secur. 2018, 2(2), 100-108